Willingness and eligibility to donate blood under 12-month and 3-month deferral policies among gay, bisexual, and other men who have sex with men in Ontario, Canada. - David J Brennan; Jp Armstrong; Maya Kesler; Tsegaye Bekele; Nathan J Lachowsky; Daniel Grace; Trevor A Hart; Rusty Souleymanov; Barry D Adam (Public Library of Science (PLoS), 2023)
In Canada, gay, bisexual and other men who have sex with men (GBMSM) are a population that are willing to donate blood, if eligible, but have a history of ineligibility and deferrals due to concerns that their blood poses an increased risk of HIV entering the blood supply. Our objective was to examine the proportion of GBMSM who are willing and eligible to donate under the 12-month deferral policy (implemented in 2016) and the 3-month deferral policy (implemented in 2019). Data for this study comes from the #iCruise study, a mixed cohort study designed to examine sexual health outreach experiences through online services and mobile apps among GBMSM in Ontario. A total of 910 participants were recruited between July 2017 and January 2018. Eligibility criteria include identify as male (cisgender or transgender); at least 14 years old; having had sex with a man in the previous year or identifying as sexually/romantically attracted to other men or identifying as gay, bisexual, queer or two-spirit; and living or working in Ontario or having visited Ontario four or more times in the past year. Participants completed a baseline and a follow-up questionnaire. A subset of #iCruise participants (n = 447) further completed this questionnaire. Willingness and eligibility to donate blood were assessed under 12-month and 3-month deferral policies. Of the 447 GBMSM surveyed, 309 (69.1%) reported a general interest in donating blood. 109 (24.4%) GBMSM were willing, 75 (16.7%) were eligible, and 24 (5.4%) were both willing and eligible to donate blood under the 12-month deferral policy. Under the 3-month deferral policy, willingness and eligibility to donate blood increased significantly to 42.3% and 29.3%, respectively. The percent of GBMSM who were both willing and eligible to donate blood also increased significantly to 12.3% under the 3-month deferral policy. The increase in willingness to donate blood varied by age, ethnicity, and geographic residence of participants whereas the increase in eligibility to donate blood varied by education level of participants. Under the 3-month deferral policy, GBMSM who were 50 years or older, identified as bisexual or other, had a lower education level, and who were not 'out' to others were more likely to be eligible to donate. GBMSM who reported a general interest in donating blood were more likely to be willing to donate blood under both deferral policies. The most common reason for not being interested in donating blood was the MSM deferral policy itself; many participants interpreted the policy as discriminatory for 'singling out' GBMSM or self-assed themselves as ineligible. Among study participants, both willingness and eligibility to donate blood was significantly higher under the 3-month deferral policy. The results suggest that a time-based reduction to a 3-month deferral policy is impactful but limited. Future research should measure GBMSM's willingness and eligibility under the individual risk-based assessment (to be implemented in 2022).